2022
DOI: 10.1101/2022.09.15.507240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene amplifications cause high-level resistance against albicidin in Gram-negative bacteria

Abstract: Antibiotic resistance is a continuously increasing concern for public health care. Understanding resistance mechanisms and their emergence is crucial for the development of new antibiotics and their effective use. Here, we report the discovery of a gene amplification-based mechanism that imparts an up to 1000-fold increase in resistance levels against the antibiotic albicidin. We show that this mechanism protects Salmonella Typhimurium and Escherichia coli by increasing the copy number of the GyrI-like transcr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
1
6
1
Order By: Relevance
“…This high-affinity binding is in line, with the previously reported binding of YgiV to the structurally related albicidin [4]. 14 In addition, due to multiple m/z shifts in the native protein MS with the mass of tested CYS derivatives, multiple binding sites per YgiV molecule seem to be possible. The exact binding mode will be further investigated by co-structure elucidation using cryo-EM and/or X-ray crystallography.…”
Section: Research Articlesupporting
confidence: 89%
See 2 more Smart Citations
“…This high-affinity binding is in line, with the previously reported binding of YgiV to the structurally related albicidin [4]. 14 In addition, due to multiple m/z shifts in the native protein MS with the mass of tested CYS derivatives, multiple binding sites per YgiV molecule seem to be possible. The exact binding mode will be further investigated by co-structure elucidation using cryo-EM and/or X-ray crystallography.…”
Section: Research Articlesupporting
confidence: 89%
“…Gene amplifications are intrinsically unstable due to higher fitness costs 16 , explaining the difference in stability of albicidin [4] and CYS resistance in E. coli, respectively. The previously investigated albicidin- [4]-resistant mutants lost their higher copy number of the respective genetic area in the absence of selective pressure 14 , whereas CYS R mutants carrying SNPs maintained high-level resistance under similar experimental conditions. Furthermore, six out of eight CYS R E. coli showed mutations in qseC, encoding for the sensor histidine kinase of the two-component system (TCS)…”
Section: Mic [µG/ml]mentioning
confidence: 87%
See 1 more Smart Citation
“…Fluoroquinolone antibiotics may thus promote the formation of genomic amplifications, and in our study, we observed pervasive generation and selection of sdrM -containing genomic amplifications upon DLX exposure. A recent study also showed that genomic amplifications of an inhibitor protein in Salmonella Typhimurium and Escherichia coli evolved upon exposure to the DNA gyrase poison albicidin which also blocks DNA religation (64), and provided albicidin resistance, further indicating that inhibition of DNA topoisomerase enzymes may aid in the formation of genomic amplifications (65).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent successes in creating analogues of cystobactamid with good antibacterial activity against K. pneumoniae by Wang et al 18 and Testolin et al 19 hold promise that it is possible to overcome this hurdle. The broad activity spectrum and its unique gyrase binding mode make albicidin an attractive lead for pharmaceutical development, despite several known (auto-)resistance mechanisms, 8,[22][23][24][25] which may be overcome by targeted engineering of the compound. 16,19,26 The resistance factor AlbA is a member of the MerR-like transcription regulator family, which typically reshape promoter DNA to induce transcription of downstream genes.…”
Section: Introductionmentioning
confidence: 99%